Stratigraphic expression of the Paleocene-Eocene Thermal Maximum climate event during long-lived transient uplift—An example from a shallow to deep-marine clastic system in the Norwegian Sea - Sømme, Tor O.; Huwe, Simone Isabelle; Martinsen, Ole J.; Sandbakken, Pål Trygve; Skogseid, Jakob; Valore, Lucas A. (Frontiers in Earth Science, 2023)
Seismic geomorphology and stratigraphic analysis can reveal how source-to-sink systems dynamically respond to climatic and tectonic forcing. This study uses seismic reflection data from the Norwegian Sea to investigate the stratigraphic response to a short-lived (0.2 Myr) period of climate change during the Paleocene-Eocene Thermal Maximum (PETM), superimposed on a long-lived (∼8 Myr) period of hinterland uplift. The data show that long-term uplift resulted in ∼300 m of relative sea-level fall, forced regression and formation of incised valleys during the latest Paleocene-earliest Eocene. The short-lived PETM climate perturbation at ∼56 Ma changed the transport dynamics of the system, allowing sediment to be bypassed to wide channel complexes on the basin floor, feeding a large mud-rich basin-floor fan more than 50 km into the basin. Our analysis also suggest that sediment supply was up to four times higher during the PETM compared to earlier and later periods. Maximum regression at ∼55.5 Ma resulted in the formation of a subaerial unconformity. The style of subaerial incision was dictated by shelf accommodation and proximity to the area of direct sediment input. Out-of-grade shelves and slopes sourced by littoral drift were prone to incision, but direct-fed and graded shelves and slopes were not. Despite maximum regression, sediments were not transported significantly beyond the toe-of-slope aprons, suggesting that rapid climate change was more efficient in bypassing sediment to the deep-water than low stands of sea level. As long-term accommodation increased after the PETM, deltas were still able to reach shelf edge, but periods of maximum regression were not associated with deep incisions along the outer shelf and only smaller canyons and gullies formed. The shelf-slope wedge was finally transgressed at ∼51 Ma. The age of deep valley incisions overlaps with the time of subaerial erosion in the East Shetland and Faroe-Shetland basins, suggesting a common mechanism for North Atlantic uplift around 55–56 Ma. Other seismic stratigraphic surfaces do not seem to be regionally time-equivalent, highlighting the importance of local controls on internal architecture of shelf-slope wedges. This study demonstrates the high-resolution stratigraphic response to long- and short-term external forcing together with intrinsic processes and can help identify similar relationships in other areas.